The Existence of Solutions for a Fractional 2m-Point Boundary Value Problems - Gang Wang; Wenbin Liu; Jinyun Yang; Sinian Zhu; Ting Zheng (Journal of Applied Mathematics)
By using the coincidence degree theory, we consider the following 2m-point boundary value problem for fractional differential equation D0+αut=ft,ut,D0+α-1ut,D0+α-2ut+et, 0<t<1, I0+3-αut|t=0=0,D0+α-2u1=∑i=1m-2aiD0+α-2uξi,u1=∑i=1m-2biuηi, where 2<α≤3,D0+α and I0+α are the standard Riemann-Liouville fractional derivative and fractional integral, respectively. A new result on the existence of solutions for above fractional boundary value problem is obtained.